ANALIS PROGRAM (NELITA CLASSMETING CARIER) SEBAGAI UPAYA MENINGKATKAN LITERASI SISWA DI SMA NEGERI dggf - Hana Nur Baiti; Rafli Rizki Setyawan; Mohammad Rabbika; Naufal Fathurrohman (Jurnal Manajemen Pendidikan, 2026)
Literacy is related to school life, as seen from the meaning of literacy itself. A simple definition of literacy is understanding or literacy. This study aims to determine the effect of the “Nelita Classmeeting Career” program implementation on increasing student literacy at SMA Negeri 6 Tangerang Selatan. The study used a qualitative approach with direct observation techniques and interviews to obtain a realistic picture of the effectiveness of the program in building students’ interest in reading and career insights. Observation results indicate that the integration of career-path concepts into classmeeting activities can create an interactive and enjoyable learning atmosphere. The availability of literacy materials relevant to the world of work and creative delivery methods contribute positively to students’ enthusiasm in seeking information. Students appear more active in discussing and looking for references regarding their future career choices. These findings confirm that school program innovations such as Nelita Classmeeting Career are important instruments in strengthening literacy culture while providing professional orientation for students at the upper secondary level.